Professional Learning Communities of Student Teachers in Internship - Theurl, Peter; Frick, Eva E.; Barrios-Espinosa, María Elvira (MDPI, 2024)
Since the early 1990s, professional learning communities (PLCs) have been widely recognized as an effective, extensively researched approach to professional development, school improvement, and student learning enhancement as well as leadership development within educational settings. Nevertheless, there remains a scarcity of research concerning the impact of this approach to professional development within the context of initial teacher education. The present study is one of the first to systematically examine the possibilities and potential of PLCs for student teachers in their practical pedagogical studies (internship). In particular, the study examines whether Student-Teacher PLCs (ST-PLCs) can be implemented in pre-teacher education and the perceptions of student teachers concerning their participation and professional learning within an ST-PLC. A total of 56 students from the University of Education Vorarlberg (Austria), the University of Málaga (Spain), and the European University Cyprus participated in the study, responding to an online questionnaire and engaging in focus-group interviews. The data collected indicated that ST-PLCs serve as a robust strategy for collaborative learning and the development of professional competencies. An analysis of the qualitative data showed that ST-PLCs are spaces where the reflection and analysis of teaching-related topics are stimulated, supported, shared, encouraged, and enhanced.
Keywords: Profesores - Formación profesional; Comunidades Profesionales de Aprendizaje; Professional Learning Communities; Collaborative learning; Pre-service teacher education; Teacher professional development